Development of a Set of Criteria for Analysing Trainee Answers in Expert Control Systems and Assessment of Knowledge - Viktoriya N. Golovachyova; Nadezhda I. Tomilova; Gulnur B. Abildaeva (National Research Mordova State University, 2019)
Introduction. The article deals with the problem of objective knowledge assessment using expert automated systems for monitoring and evaluating knowledge. The relevance of this study is determined by qualitatively improving the monitoring and evaluation of knowledge using a testing method. The purpose of the work was to develop a set of criteria for analysing a test response along with an objective approach to their assessment. Materials and Methods. The study was conducted on the basis of the system analysis and B. Bloom's method tracking learning outcomes, as well as the method widely used in the study of the quality of studies on the assessment of educational achievement of students: Program for International Student Assessment. In order to study the problem, 102 teachers and 357 students of two universities - Karaganda State Technical University and Karaganda State University named after E.A. Buketov - in Karaganda, Kazakhstan were interviewed and their responses observed. Results. The results of the work are of interest to the scientific and pedagogical community, as well as practicing teachers. The article proposes a new approach to constructing a test question to allow a response in a freely-constructed form. Such an answer can be analysed by a set of criteria for its formation based on the developed algorithms for a criterial assessment of their quality. This makes it possible to apply the obtained results to solve the scientific problem of objective k nowledge assessment using testing. Discussion and Conclusion. The completed study has expanded the representation of the possibilities of using the expert systems for monitoring and evaluating knowledge and increasing the objectivity of knowledge acquired during learning processes. The received results represent the practical importance for teachers involved in the development of expert control systems and assessment of knowledge. The prospect of further study consists in improving the testing method by expanding the set of criteria for assessing knowledge.